(untitled) - Stamp, L. Dudley (London, 1960)
This book deals with one of the outstanding problems today; how to increase the wealth of the so-called under-developed countries.
Keywords: Dân số,Cung cấp thực phẩm,Natural resources,Population,Food supply,Tài nguyên thiên nhiên